The Impact of Capital Adequacy Ratio, Credit Risk, Market Risk, Financial Distress, and Macroeconomic Toward Stock Return With Audit Quality as Moderator - Harsono Yoewono; Stefanus Ariyanto (Accounting and Finance Studies, 2022)
This study was conducted to analyze the effect of capital adequacy ratio, credit risk, market risk, financial distress, inflation, and the exchange rate on stock returns with audit quality as moderating. The object of this research is companies in the banking sector listed on the Indonesia Stock Exchange for the period 2015-2020. This research was conducted with the aim of explaining quantitatively the attitude tendency of the population by examining a sample of the population. The research data is included in the type of secondary data in the form of financial reports and bank annual reports book 3 and book 4 of the implementation of Basel during the period 2015-2020. The data was obtained from the Indonesia Stock Exchange website, namely the website www.idx.co.id. The data analysis method used in this study uses panel data regression with the help of the Eviews 10 program. The results of this study conclude that the capital adequacy ratio, market risk, financial distress, inflation, exchange rate, and audit quality have no effect on stock returns. However, credit risk has an influence on stock returns. In this study there is a moderating variable, obtained audit quality as a moderating variable does not affect the relationship between capital adequacy ratio, market risk, financial distress, inflation, and the exchange rate to stock returns. However, audit quality as a moderating variable is able to influence the relationship between credit risk and stock return.